2018
DOI: 10.17116/patol20188043
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus and Epstein-Barr virus in the pathogenesis of inverted papilloma and associated sinonasal carcinoma

Abstract: Taking into account the low HPV DNA concentration detected only for types 6 and 11, as well as the immunohistochemical detection of HPV L1 in the tumor stromal lymphocytes and macrophages and some basal epitheliocytes in individual cases, it can be assumed that HPV does not play a crucial role as an etiological factor for IP. PCR revealed oncogenic HPV types 16 and 35 in sinonasal carcinoma associated with IP only in one case, which makes it untimely to claim that this virus plays a very special role in the et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…8 Likewise, Bakhtin et al concluded that HPV did not play a crucial role in the etiology of inverted papilloma. 28 The present study results were consistent with those previously published, but our findings revealed that HPV was associated with recurrent SNIP.…”
Section: Discussionsupporting
confidence: 94%
“…8 Likewise, Bakhtin et al concluded that HPV did not play a crucial role in the etiology of inverted papilloma. 28 The present study results were consistent with those previously published, but our findings revealed that HPV was associated with recurrent SNIP.…”
Section: Discussionsupporting
confidence: 94%
“…Although the relationship of HPV infection to malignant transformation remains somewhat controversial [68,82], a recent meta-analysis by Zhao et al found a close association between HPV infection and malignancy, with a pooled odds ratio of 2.16 [83]. Furthermore, high-risk subtypes HPV-16, HPV-18, and HPV-16/18 coinfection had even stronger correlations, with odds ratios of 8.8, 8.04, and 18.57 respectively.…”
Section: Viralmentioning
confidence: 99%